2009
DOI: 10.1002/app.29787
|View full text |Cite
|
Sign up to set email alerts
|

Improving interfacial adhesion between thermoplastic polyurethane and copper foil using amino carboxylic acids

Abstract: A chemical methodology to improve the adhesion between copper foil and a thermoplastic polyurethane (TPU) matrix is reported. The copper foil (0.127 mm thickness) was treated with aminocarboxylic acid‐based coupling agents such as 6‐aminohexanoic acid and 4‐aminobenzoic acid. 3‐Aminopropyl trimethoxysilane was also used as a conventional silane coupling agent for comparative studies. The interfacial adhesion between copper foil and laminated TPU was examined by means of peel adhesion test, scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…As the bonding clearance increases, significant decreases were observed in the static and dynamic strengths. Based on the studies of carbon fiber reinforced composites bonded to steel plates, Oehlers, Liu and Seracino [ 6 ] revealed that debonding generated by shear deformation is the primary form of failure in adhesively bonded structures. Tantikom, Aizawa and Mukai [ 7 ] reported their work on symmetric to asymmetric deformation transition in regular cellular materials.…”
Section: Hybrid Composite Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the bonding clearance increases, significant decreases were observed in the static and dynamic strengths. Based on the studies of carbon fiber reinforced composites bonded to steel plates, Oehlers, Liu and Seracino [ 6 ] revealed that debonding generated by shear deformation is the primary form of failure in adhesively bonded structures. Tantikom, Aizawa and Mukai [ 7 ] reported their work on symmetric to asymmetric deformation transition in regular cellular materials.…”
Section: Hybrid Composite Materialsmentioning
confidence: 99%
“…Improvement of the reliability of hybrid composite materials relies on the enhancement of polymer/metal interface bonding. Various surface treatments including alkaline etching and acid pickling (applied separately or in combination with phosphoric acid anodizing) [ 19 ], plasma processing [ 20 23 ], ion beam irradiation [ 24 26 ], and coupling agent treatment [ 27 ] have been explored to examine the effect of pre-treatment on the adhesive bonding between metals and polymers. It is found that the presence of oxide and small molecules such as water in the interface region is responsible for the degradation of bonded joints [ 19 ].…”
Section: Hybrid Composite Materialsmentioning
confidence: 99%
“…In the present study, wool fabric was treated with LTA nano‐zeolite (100 nm) to improve the fabric's surface hydrophilicity or wettability and associated performance, while retaining the intact zeolite structure. As silane effectively binds two otherwise poorly compatible surfaces with different functional groups, 3‐mercaptopropyl trimethoxysilane was used as a coupling agent to bind the inorganic zeolite to the organic wool fabric.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main problems that has to be addressed when coating polyurethanes concerns the low adhesion forces present at metal/polyurethane interfaces . On the other hand if we can prepare successfully metal coatings on polyurethanes we can easily transfer the results to many other polymers excluding the highly fluorinated materials .…”
Section: Introductionmentioning
confidence: 99%